2018
DOI: 10.1186/s40780-018-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between warfarin and short-term intravenous amiodarone in intensive care unit patients after cardiac surgery

Abstract: BackgroundAmiodarone and warfarin are sometimes administered immediately after cardiac surgery. Although the interaction between long-term oral amiodarone and warfarin has been reported, the interaction between warfarin and short-term intravenous amiodarone has not been reported. In this study, we investigated the effect of short-term intravenous amiodarone on the anticoagulant effect of warfarin in patients who underwent cardiac surgery.MethodsWe retrospectively reviewed the medical records of 11 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…32 The first patient was also initiated on amiodarone before adding rifampin, 32 which is known to inhibit warfarin metabolism and reduce warfarin dose requirement. 45 Interestingly, in consistence with most of the previously reported cases, our data showed that the mean required warfarin dose to attain the target INR in the responders group was 10.4 mg.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…32 The first patient was also initiated on amiodarone before adding rifampin, 32 which is known to inhibit warfarin metabolism and reduce warfarin dose requirement. 45 Interestingly, in consistence with most of the previously reported cases, our data showed that the mean required warfarin dose to attain the target INR in the responders group was 10.4 mg.…”
Section: Discussionsupporting
confidence: 85%
“…Another recent case series showed successful target attainment at a median of 30 days following rifampin addition to warfarin by 6 out of 7 patients at daily doses of 5.5, 9.5, 12.5, 16, 20, and 33 mg; which were increased from baseline requirements of 3.5, 3, 3, 8.5, 10.7, and 8.4 mg, respectively 32 . The first patient was also initiated on amiodarone before adding rifampin, 32 which is known to inhibit warfarin metabolism and reduce warfarin dose requirement 45 . Interestingly, in consistence with most of the previously reported cases, our data showed that the mean required warfarin dose to attain the target INR in the responders group was 10.4 mg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For warfarin combined with amiodarone, several studies demonstrate that amiodarone has a significant effect on the anticoagulant effect of warfarin 31 , 32 . In this study, it shows that when patients are combined with amiodarone, the EC50 value of the anticoagulant effect will decrease by 0.602 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…The patient underwent emergency surgery for a partial small intestine resection and colostomy with a diagnosis of nonocclusive mesenteric ischemia. A PT-INR/dose of WF ratio 13) was used to rule out dose-dependent changes in anticoagulant effects and to confirm effects on metabolic processes. This work was approved the University of the Ryukyus Ethics Review Committee (Approval No.…”
Section: Introductionmentioning
confidence: 99%